Model home - Solomon, Rivers (MCD / Farrar, Straus and Giroux, 2024)
"The Maxwell siblings return to their childhood home in the Dallas suburbs after the shocking news of their parents' death. They return to find the house, and the family itself, haunted by strange, inexplicable terrors"--